Black ginger (Kaempferia parviflora) extract enhances circadian rhythm and promotes lipolysis in mice fed a high-fat diet - Izumi Yoshida; Takashi Mishima; Momochika Kumagai; Yushi Takahashi; Kazuhiro Fujita; Tomoji Igarashi (Journal of Functional Foods, 2023)
Circadian rhythms are endogenous oscillations that regulate physiological and biochemical processes with approximately 24-h rhythms. Circadian rhythmic disorders caused by a high-fat diet (HFD) are associated with metabolic syndrome and obesity. Herein, we assessed whether black ginger (Kaempferia parviflora) modulates disturbances in the circadian rhythm and improves obesity caused by an HFD in C57BL/6 mice. Three study groups were created: normal diet, HFD, and HFD + K. parviflora extract (KPE). HFD-fed mice showed attenuated circadian locomotor activity, weight gain, and increased serum triglyceride and cholesterol levels, whereas HFD mice administered KPE showed improved circadian locomotor activity and reduced body weight and serum triglyceride levels. Moreover, following RNAi knockdown of clock genes in 3T3-L1 adipocytes, KPE was found to enhance clock gene expression and induce lipolysis-related gene expression in adipocytes. Collectively, these results suggest that KPE improves rhythm disturbances in HFD-fed mice and exhibits anti-obesity effects.